Establishment of a non-permanent GPS network to monitor deformations in Zafarraya Fault and Sierra Tejeda Antiform (Spain) - Borque Arancón, María Jesús; Galindo-zaldívar, Jesús; Gil Cruz, Antonio J.; Jabaloy Sánchez, Antonio; Lacy Pérez de los Cobos, M. Clara de; López Garrido, Ángel Carlos; Rodríguez Caderot, Gracia; Ruiz Armenteros, Antonio; Sanz de Galdeano Equiza, Carlos (Física de la Tierra, 2005)
The NW-SE to NNW-SSE convergence between the African and Eurasian plates in the western Mediterranean has developed the recent relief of the Betic-Rif Cordilleras. The central part of the Internal Zones of the Betic Cordilleras is deformed by large open folds and faults, mainly with normal character. The Zafarraya fault, located to the N of the Sierra Tejeda antiform, was active during the 1884 Andalusia earthquake of 6.7 estimated magnitude. In the framework of an interdisciplinary research project, a non-permanent GPS-network has been established at Zafarraya Fault and Sierra Tejeda antiform to monitor deformations related to these active tectonic structures.